Analysis of Marketing Strategy at Nagoyaramen - Diklusari Isnarosi Norsita; Ratih Hardiyanti (Agroindustrial Journal, 2017)
Nagoyaramen is a franchise ramen restaurant. Nagoyaramen was switching business location, so they needed information about target and market segments which would affect the marketing strategy. The purpose of the study was (1) Analyzing and defining market segments of Nagoyaramen. (2) Formulating marketing strategies of Nagoyaramen in accordance with the selected segment. The primary data collection was done through questionnaire. This study used descriptive analysis such as Importance-Performance Analysis method and cluster analysis. Interview was used to choose the best strategy. Cluster analysis resulted in dividing costumers into three segments, namely a perfectionist, tasteful, and socialist. We picked the perfectionist which covers 60.66% of customer. This particular segment is concerned with almost all attributes of marketing mix. The group was predominantly female (71.43%), work as a student (45.05%), age range 17-24 years (52.75%), and last education high school (43.96%). Strategies offered are location approaching schools or colleges, affordable prices, promotion through fliers and giving discounts, Japanese ornaments must remain there as a hallmark of Nagoyaramen, Japanese ornament on the nameplate, taste of the product should be maintained, maintaining a varied menu, and speeding up the service around lunch break. So the best strategy chosen by the owner is location approaching schools or colleges.